Cooperative Integrated Reading and Composition (CIRC) and Jigsaw: Which is More Effective on EFL Reading - Arisman, Rizal (International Journal for Educational and Vocational Studies, 2019)
The objective of this research was to find out the significant difference of two learning method from cooperative learning; those are Cooperative Integrated Reading and Composition (CIRC) and Jigsaw method and which method is more effective in EFL reading comprehension. This research used a quantitative approach by applying a quasi-experimental method. The data were collected from two classes at grade eight students of SMP Negeri 3 Baubau, Southeast Sulawesi in the school year of 2018/2019 using test. The test was applied twice; those were pretest and posttest for each class. The results indicated that there was not any significant difference in EFL reading comprehension between CIRC and Jigsaw group. But, the range between pretest and posttest for each class indicated the Jigsaw method was more effective than the CIRC group since the mean score of EFL reading comprehension in Jigsaw group was greater than the CIRC group.